EFEKTIVITAS PENAGIHAN PAJAK DENGAN SURAT TEGURAN DAN SURAT PAKSA TERHADAP PENERIMAAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA KUALA TUNGKAL - Earlistiani Kardianti; Muhammad Hidayat; Trie Sartika Pratiwi (Jurnal Ilmiah Ekonomi Global Masa Kini)
Tax is one of revenue sources that contributes greatly to the state. Tax arrears are the amount of tax payable that have not been paid by the taxpayer. The high amount of tax arrears will result in reduced tax revenue. Therefore, an active billing action against tax arrears should be taken, tax collection with Warning Letters and Tax Warrants is an action taken by the government to raise awareness of the taxpayer in carrying out their obligation to pay the payable tax.  The high rate of arrears makes the government try to maximize tax revenue by issuing warning letters and tax warrants. This study aims to determine the level of effectiveness and contribution of tax collection with warning letters and tax warrants against increased tax revenue in tax office. The method used in this research is descriptive method to give an idea whether tax collection with warning letters and tax warrants has been effective and how much contribution given to the total of tax revenue. The results show that the collection of taxes with warning letters and tax warrants in 2015-2016 are classified as ineffective and has given less contribution to the tax revenue.Keywords : Effectiveness, Collection of tax arrears, Warning letter, Tax warrant